An economic Evaluation of training and its Effect on employee performance in Building Construction Directory of Sulaimani province – Kurdistan region - Younis A.Ahmed; Dalia Khalid Faeq (QALAAI ZANIST JOURNAL, 2020)
Training would provide opportunities to the employees to have a better career life and get better position in the organization. This paper attempts to investigate the effect of training on employee performance. Likewise, for answering study questions “Whether training has a vital effect on employee Performance of Building Construction directory of Sulaimani province - Kurdistan region? To achieve this objective and answering this question , the descriptive analytical method with linear regression model were applied , and the data collected through primary source that are from questionnaires of (70) employees which working in Building Construction Directory of Sulaimani province.The results show that dimensions of training has a strong positive significant influence on employee performance and the regression coefficient of responsiveness is 0.76 with p-value of 0.000, which indicates that the increase in training level by one percent, employee performance increases by 0.76 percent. To conclude, some of suggestion provides to help managers of Building Construction Directory of Sulaimani province to offer regular and different levels of training to guarantee employee desires and incrase work performance.